PENANGGULANGANPENGANGGURAN MELALUI PENINGKATAN KETERAMPILAN WlRA USAHA DAN EKONOMI PRODUKTIF DIDAERAHISTIMEWA YOGYAKARTA - Soenarto Soenarto (LPMPP Universitas Negeri Yogyakarta, 2002)
This article is based on a research conducted to know the implementation and result of the New Entrepreneurs' Training (NET) and the Productive Economic Institution Training (PElT) held as some of the efforts to solve the problem of unemployment handled by the part of the Social Security Network Program taken care of by the Province of the Yogyakarta Special Territory's Regional Office ofthe Employment Department. The focus of the research was on determining how far the training programs could help overcome the unemployment in particularly that province as a result of Indonesia's recent economic crisis. All the 1140 trainees became the research populatioILand 450 of them were taken as a proportional sample. The data were obtained by means ofa questionnaire composed on the basis of adifferential semantic scale. From the research it is found that (1) the NET has produced good results, with 88% of the trainees having produced proposals for the establishment of new business companies complete with planned programs and costs and 66% of the trainees having already started running their business; (2) the business companies started have good prospects in the current situation of crisis and the degree ofhow well they run is categorized moderate; (3) the knowledge. and skills acquired in the training suit the trainees' needs and are beneficial to them in runningtheir business; (4) further intensive guidance and advisory assistance fortrainees as the follow-up of the training are also made available bythe institution conducting the training; (5) the PEIT has produced moderately good results, with 60% of the trainees having been absorbed, channeled, and positioned as employees at companies they are apprenticed to or at companies pioneered by the NET; (6) 40% ofthe trainees have not received employment because they have refused the positions found for them for the reason that the salary offered has been lower than the required Regional Minimum Fee, because of the economic slump, and because of no fault of the institution conducting the training; (7) the knowledge and skills acquired in the training suit the trainees' needs and beneficially arm them in looking for work; and (8) the apprenticeship and guidance programs run by the institution conducting the training are running moderately well and extremely helpful in job seeking.